Calculation of force and power during bench throws using a Smith Machine: The importance of considering the effect of counterweights - Kobayashi, Y.; Narazaki, K.; Akagi, R.; Nakagaki, K.; Kawamori, N.; Ohta, K. (International Journal of Sports Medicine, 2013)
For achieving accurate and safe measurements of the force and power exerted on a load during resistance exercise, the Smith machine has been used instead of free weights. However, because some Smith machines possess counterweights, the equation for the calculation of force and power in this system should be different from the one used for free weights. The purpose of this investigation was to calculate force and power using an equation derived from a dynamic equation for a Smith machine with counterweights and to determine the differences in force and power calculated using 2 different equations. One equation was established ignoring the effect of the counterweights (Method 1). The other equation was derived from a dynamic equation for a barbell and counterweight system (Method 2). 9 female collegiate judo athletes performed bench throws using a Smith machine with a counterweight at 6 different loading conditions. Barbell displacement was recorded using a linear position transducer. The force and power were subsequently calculated by Methods 1 and 2. The results showed that the mean and peak power and force in Method 1 were significantly lower relative to those of Method 2 under all loading conditions. These results indicate that the mean and peak power and force during bench throwing using a Smith machine with counterweights would be underestimated when the calculations used to determine these parameters do not account for the effect of counterweights.